Afforestation Works in Poona and Satara Divisions, Bombay State - Thakekar, K. N. (Indian Forester, 1958)
The History of Reserved Forests managed by the Forest Department till about 1910-11 and then handed over to Revenue Department is given and the defects of this transfer pointed out. Some of these areas have been taken over from the Revenue Department in Ahmednagar and Sholapur Districts under the administrative control of Poona and Satara Divisions and the afforestation works undertaken on a large scale at specific forest areas under the auspices of the Second. Five-Year Plan. The results of these afforestation works have been narrated in short in this article.